Unraveling The Proteome Changes Underlying Insecticides Resistance In The Dengue Vector Aedes Aegypti Using Quantitative Proteomics Analyses - Abubakar, Shettima (2023)
Aedes aegypti is a significant vector for many tropical and subtropical flavivirus diseases. Synthetic insecticides are the primary vector control method. However, the widespread use of pyrethroid is causing resistance in Ae. aegypti. Hence, this study was aimed to elucidate permethrin and temephos resistant protein expression profiles in Ae. aegypti using quantitative proteomics. The study evaluated the susceptibility status of Ae. aegypti from dengue hotspot and non-hotspot areas of Penang Island against 0.75% permethrin and 31.25 mg/l temephos using the world health organisation (WHO) standard bioassay protocols. Protein extracts from the mosquitoes were analysed using LC–ESI–MS/MS for protein identification and quantification via label-free quantitative proteomics (LFQ). The study used Perseus 1.6.14.0 statistical software to perform differential protein expression (DEP) analysis via ANOVA and student’s T-test. The t-test selected proteins that showed ≥2.0-fold change (FC) and ≥2 unique peptides were used for gene expression via qPCR. The study also used STRING software for functional ontology enrichment and proteinprotein interaction (PPI) analyses. Bioassay results showed 28% and 53% mortalities in mosquitoes exposed to permethrin from the hotspot and non-hotspot areas. The susceptibility of Ae. aegypti larvae revealed high resistance to temephos in hotspot and non-hotspot areas with 80% and 91% mortalities. The LFQ analysis revealed 501 and 557 (q-value <0.05) DEPs in adults and larvae Ae. aegypti.